(3EQTGO QjH Edi eYQaI GdCOjHs - (3jGbhJ Hf YHO Gddg GdQhej GdMehj, TgGH GdOjf CHh YHO Gddg,J (B626 (3g` s ((3CMeO Hf eMeO GdOgThQi s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdbOQI GdbGgQI hHYO aeGRGdJ efP ZPjJ HZQGe GdCOH aeG hLOJ ai Pdc JUfjakG TGajkG hdG JCdjakG cGajG s
(3BNQgG (B:s
(3JQLeI GdMSf Hf ejehf GdfUQi CMO Hfi fUQ Hf JYjf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B131 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B178s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs